Comparison of game-related statistics in men's international championships between winning and losing teams according to margin of victory - Saavedra, J. M.; Escalante, Y.; Madera, J.; Mansilla, M.; Garcia-Hermoso, A. (Collegium Antropologicum, 2014)
The aims of this study were (i) to compare water polo game-related statistics by game outcome (winning and losing teams) and margins of victory (close games, unbalanced games, and very unbalanced games), and (ii) to identify characteristics that mark the differences in performances for each group of margin of victory. The game-related statistics of the 308 men's matches played in seven International Championships (Olympic Games, World and European Championships) were analysed. A cluster analysis established three groups (close games, unbalanced games, and very unbalanced games) according to the margin of victory. Differences between game outcomes (winning or losing teams) and margins of victory (close, unbalanced, and very unbalanced games) were determined using the chi-squared statistic, also calculating the effect sizes of the differences. A discriminant analysis was then performed applying the sample-splitting method according to game outcome (winning and losing teams) by margin of victory. It was found that the game-related statistics differentiate the winning from the losing teams in each final score group, with 7 (offensive and defensive) variables differentiating winners from losers in close games, 16 in unbalanced games, and 11 in very unbalanced games. In all three types of game, the game-related statistics were shown to discriminate performance (85% or more), with two variables being discriminatory by game outcome (winning or losing teams) in all three cases: shots and goalkeeper-blocked shots.